The Political Trial, the Political Pre-Trial and the Vacancy due to Moral Incapacity: brief notes on the Responsibility of the President of the Republic in the Peruvian Constitution of 1993 - Muñoz Cabrera, Christian (2022)
The present work deals with the study of the responsibility regime of the President of the Republic in the Peruvian Constitution of 1993. To this end, the article will analyze, both from a historical and comparative approach, the figures of the political trial, the political pre-trial and the vacancy due to moral incapacity. In this way, the paper begins by reviewing the historical origins of impeachment in Anglo-Saxon systems of government. Subsequently, it studies the way in which this figure was adopted in the Peruvian model, as well as its historical development. Finally, this study focuses on the analysis of the presidential vacancy due to moral incapacity, proposing a way of understanding this figure and some reform alternatives.